2021
DOI: 10.1038/s41556-021-00699-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical compartmentalization of the intestinal organoid enables crypt folding and collective cell migration

Abstract: Intestinal organoids capture essential features of the intestinal epithelium such as crypt folding, cellular compartmentalization and collective movements. Each of these processes and their coordination require patterned forces that are currently unknown. Here we map three-dimensional cellular forces in mouse intestinal organoids grown on soft hydrogels. We show that these organoids exhibit a non-monotonic stress distribution that defines mechanical and functional compartments. The stem cell compartment pushes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 69 publications
3
68
0
Order By: Relevance
“…Despite the high degree of the physiological relevance of organoid technology, similar to any other system, it has its own limitations: Along with being a highly variable and heterogeneous system due to clonal or inter-patient variability, there remains a lack of standardization in 3D culture maintenance and further downstream analysis [ 214 ]. Moreover, limited optical accessibility of these models often impairs organoid mechanobiology studies [ 215 ]. Most critically, they are prone to diverge from their original tissue status and lose their cellular identity over time [ 215 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the high degree of the physiological relevance of organoid technology, similar to any other system, it has its own limitations: Along with being a highly variable and heterogeneous system due to clonal or inter-patient variability, there remains a lack of standardization in 3D culture maintenance and further downstream analysis [ 214 ]. Moreover, limited optical accessibility of these models often impairs organoid mechanobiology studies [ 215 ]. Most critically, they are prone to diverge from their original tissue status and lose their cellular identity over time [ 215 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, limited optical accessibility of these models often impairs organoid mechanobiology studies [ 215 ]. Most critically, they are prone to diverge from their original tissue status and lose their cellular identity over time [ 215 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our understanding of organoid mechanobiology was limited because of the limitations of the analytical methods, a recent study confirmed a substantial agreement between organoids and the intestinal epithelium in vivo. 3 Intestinal organoids can capture the cellular morphology and cytoskeletal organization of the in vivo crypt structure. Obviously, in vivo comparison is necessary for the first validation that organoids reflect the in vivo state.…”
mentioning
confidence: 99%
“…Obviously, in vivo comparison is necessary for the first validation that organoids reflect the in vivo state. There are a variety of ECM/scaffolds used in organoid research, such as Matrigel (Corning Life Sciences, Tewksbury, MA), 2 collagen gel, 1 hydrogel, 3 the decellularized human intestinal scaffolds, 4 and the perfusable tube scaffolds emulating crypt structures. 5 These ECM/scaffolds may support organoid formation resembling in vivo crypt structures.…”
mentioning
confidence: 99%
“…Shape formation of tissues and organs during embryogenesis is a long-standing, fascinating problem of developmental biology. Since cells are the functional units of a tissue, shapes in the organs must originate at the cellular level [2][3][4][5]. Cell shapes are vital in both health and disease.…”
mentioning
confidence: 99%